Projecto de Comportamento Térmico. Estudo de Sensibilidade sobre Certificação Energética em Edifícios Existentes - Alberto César Almeida Gonçalves da Silva (2008)
This research was performed under the Integrated Master's degree in Civil Engineering in specialization of Civil Construction and its main objective was to evaluate the influence of climatic aspects and the equipment used for heating hot water and sanitary (electricity or gas fuel energy), the geometry and environment of the buildings, which classifies the energy of residential buildings in Portugal, therefore this was intended analyze the weight of each of these parameters in the energy certification in existing buildings.The strategy was a study of sensitivity of the four parameters described above, encompassing a wide range of cases that reflect the Portuguese reality constructive.Therefore as a result each parameter simulated were remaining stabilized, thus making sure that the results that were obtained were stated as the parameter under study. This methodology was followed for the other three parameters bearing in mind the primary objective of reviewing the changes made to the energy index Ntc/Nt by each parameter.At a later stage were analyzed the results obtained, as they went about drawing conclusions from the influence of each of the parameters studied in the final weight of the energy certification.Finally, given the results and conclusions withdrawn from the study, there was a critical comment made of the existing buildings certification.Keywords: Geometry, climate, environment, equipment, energy certification.